Efficacy of an extensively hydrolyzed formula with the addition of synbiotics in infants with cow's milk protein allergy: a real-world evidence study - Soria, Ramiro; Del Compare, Mónica; Sallaberry, Marisa; Martín, Graciela; Aprigliano, Gustavo; Hermida, Verónica; Carosella, Mabel; Gruenberg, Martín; Monsell, Silvana; Micone, Paula; Maciero, Eugenia; Giglio, Norberto (Frontiers in Allergy, 2023)
Introduction: Cow's milk protein allergy (CMPA) is a common food allergy in early childhood, and extensively hydrolyzed formulas (EHF) are the preferred treatment for infants requiring breastmilk substitutes. However, limited data exist on the evolution of initial symptoms in infants newly diagnosed with CMPA treated with EHF with added synbiotics. This real-world evidence study aimed to evaluate symptom resolution in these infants after 4 weeks of treatment and assess its impact on the family's quality of life. Materials and Methods: This observational, longitudinal, and prospective study included 65 patients completing the 28-day intervention phase with EHF and synbiotics. Treating physicians recorded child´s anthropometry, Infant Gastrointestinal Symptoms Questionnaire (IGSQ-13), and CoMiSS (Cow´s Milk Allergy Symptoms Score) at baseline and after 28 days. Caregivers reported child´s regurgitation, stools, PO-SCORAD (Patient Oriented Scoring of Atopic Dermatitis), and FAQL-PB (Family Quality of Life - Parental Burden) during treatment. Data were collected through Google Forms and analyzed using STATA. Results: After treatment, 95.4% of patients showed improvement or disappearance of overall initial symptoms. Gastrointestinal symptoms improved or disappeared in 92% of patients, and dermatological symptoms improved or disappeared in 87.5%. The median CoMiSS dropped from 9 to 3, and no patient exceeded the 12-cut-off point. The median PO-SCORAD dropped from 11.5 to 1. The treatment reduced stool frequency, improved consistency, and decreased regurgitation frequency. The percentage of patients without regurgitation increased from 11% to 31%. Infants' sleep pattern and family quality of life significantly improved. Conclusion: The use of an EHF with synbiotics for infants with CMPA suggested a good safety profile, an adequate infant growth, and improvement of overall, gastrointestinal, and dermatological symptoms. It also suggested a lower daily frequency of regurgitations and stools, and an improvement in stool consistency, sleeping pattern, and quality of life of the infant and his family.